Experimental evaluation of WBAN antenna performance for FCC common frequency band with human body - Noitubtim, Musleemin; Deepunya, Chairak; Promwong, Sathaporn (My University, 2013)
Wireless communication systems have become important in daily life such as wireless body area network (WBAN). An ultra-wideband (UWB) technology is chosen to be used for short-range communication scenarios, low-power and high data rate technology which accommodates appropriate technology in WBAN. In this paper, we design a printed circular monopole with coplanar waveguide (CPW) fed for WBAN with common frequency band following FCC common band (7.25-8.5 GHz). The antenna structure is simple, using FR4 circuit board (PCB) with overall size of 18 × 20 × 1.6 mm3. The simulation and experiment results show that the proposed antenna achieves good impedance matching and stable radiation patterns over operating bandwidth of 6.8-12.34 GHz. Moreover, the authors evaluate UWB antenna in two scenarios are free-space and with human-body to consider the antenna performance in time domain. © 2013 Springer Science+Business Media Dordrecht(Outside the USA).
Keywords: BAN; Human body; UWB; WBAN; Wideband antenna